2014
DOI: 10.1021/jp510037c
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Computational Investigation into the Gas-Phase Acidities of Tyrosine and Phenylalanine: Three Structures for Deprotonated Tyrosine

Abstract: Using mass spectrometry and correlated molecular orbital theory, three deprotonated structures were revealed for the amino acid tyrosine. The structures were distinguished experimentally by ion/molecule reactions involving proton transfer and trimethylsilyl azide. Gas-phase acidities from proton transfer reactions and from G3(MP2) calculations generally agree well. The lowest energy structure, which was only observed experimentally using electrospray ionization from aprotic solvents, is deprotonated at the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 86 publications
3
25
0
Order By: Relevance
“…Third, by adopting the supramolecule/continuum approach, we simulate the structures of perm β-CD/H + /L-Lys complex in solution, thereby finding that the relative thermodynamic stability of perm β-CD/H + /L-Lys complex in solution is the complete reversal of that in the gas phase: The extremely higher Gibbs free energy gas phase structure (Complex I) corresponds to the most stable conformer (Complex A) in solution, and the most stable gas phase conformer (Complex II) becomes a less stable one (Complex B) in solution. This clearly indicates that the origin of the high Gibbs free energy gas phase structure (Complex I) is the configuration (Complex A) of perm β-CD/H + /L-Lys in solution , suggesting that the structure of gas phase host–guest complexes produced by ESI/MS/IRMPD technique 43 may be used as a very useful and accurate guide for probing host–guest–solvent interaction in solution.…”
Section: Introductionmentioning
confidence: 96%
“…Third, by adopting the supramolecule/continuum approach, we simulate the structures of perm β-CD/H + /L-Lys complex in solution, thereby finding that the relative thermodynamic stability of perm β-CD/H + /L-Lys complex in solution is the complete reversal of that in the gas phase: The extremely higher Gibbs free energy gas phase structure (Complex I) corresponds to the most stable conformer (Complex A) in solution, and the most stable gas phase conformer (Complex II) becomes a less stable one (Complex B) in solution. This clearly indicates that the origin of the high Gibbs free energy gas phase structure (Complex I) is the configuration (Complex A) of perm β-CD/H + /L-Lys in solution , suggesting that the structure of gas phase host–guest complexes produced by ESI/MS/IRMPD technique 43 may be used as a very useful and accurate guide for probing host–guest–solvent interaction in solution.…”
Section: Introductionmentioning
confidence: 96%
“…Although the GAs of amino acids have been the focus of several studies, 1,2,17,35,36 the only previous report of GAs for amino acid amides is our work with glutamic acid amide and aspartic acid amide. 2 In this prior report, our experimental and computational G3(MP2) level GA values were in excellent agreement, and the calculations confirmed that both amides undergo side chain deprotonation at their carboxylic acid groups.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reference compounds were introduced through a leak value at constant pressures, which were in the range of (1.0−11) × 10 −8 mbar. Ion/ molecule reaction times in the FT-ICR cell were varied from 0 to 300 s. Pressures were measured by a calibrated ion gauge, 17,40 and the pressure of each reference compound was corrected for its ionization efficiency, 41 which is determined by polarizabilities calculated with atomic hybrid parameter procedures. 42 The pseudo-first-order decay of precursor ion intensity as a function of reaction time was utilized to obtain experimental rate constants from which GA values were assigned.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[16] Furthermore, competing gas-phase (de)protonation sites can have important analytical implications. For instance, if relative abundances of the (de)protonation sites are dependent on experimental conditions, so too might be the observed spectra from tandem mass spectrometry,[7] ion mobility,[8, 9] or infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%